OCT embedded sections of pathological specimens as a source of high quality RNA for reverse transcriptase/polymerase chain reaction. Issue 3 (March 1996) - Irving, J A; Cain, G; Parr, A; Howard, M; Angus, B; Cattan, A R
Abstract : OCT embedded cryostat sections of stored pathological specimens of non-Hodgkin's lymphoma were used to provide RNA. After reverse transcription to produce cDNA, the polymerase chain reaction was performed with primers for standard and variant forms of the CD44 molecule. Using Southern transfer and hybridisation with a probe specific for exon 4 of the CD44 gene, both standard and variant forms were visualised by autoradiography. This method was shown to be applicable to other gene products by using primers specific for the abl and bcr genes. This technique permits retrospective analysis of RNA from small amounts of stored pathological samples.